2020
DOI: 10.1001/jamaoncol.2020.0726
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor Rechallenge After Immune-Related Adverse Events in Patients With Cancer

Abstract: IMPORTANCE Limited information is available on the safety of a rechallenge with an immune checkpoint inhibitor (ICI) after an immune-related adverse event (irAE).OBJECTIVE To identify the recurrence rate of the same irAE that prompted discontinuation of ICI therapy after an ICI rechallenge in patients with cancer and to identify the clinical features associated with such recurrences. DESIGN, SETTING, AND PARTICIPANTS This observational, cross-sectional, pharmacovigilance cohort study examined individual case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
313
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 364 publications
(368 citation statements)
references
References 23 publications
(58 reference statements)
13
313
2
Order By: Relevance
“…This study showed no statistically significant difference in the incidence of irAEs, and the irAE profile was similar in both groups. 41 Another study evaluating safety and efficacy of ICI treatment in real life conditions showed no difference in OS, PFS, or irAEs between patients older than 70 years old or younger patients. 84 However, Baldini et al analysed patients treated with anti-PDL-1 therapy and showed an increase in the incidence of grade 2 or higher AEs in patients older than 70 years (33% versus 25%, p = 0.03).…”
Section: Immunotherapy In High Risk Populations Patients With Auto Immentioning
confidence: 99%
See 4 more Smart Citations
“…This study showed no statistically significant difference in the incidence of irAEs, and the irAE profile was similar in both groups. 41 Another study evaluating safety and efficacy of ICI treatment in real life conditions showed no difference in OS, PFS, or irAEs between patients older than 70 years old or younger patients. 84 However, Baldini et al analysed patients treated with anti-PDL-1 therapy and showed an increase in the incidence of grade 2 or higher AEs in patients older than 70 years (33% versus 25%, p = 0.03).…”
Section: Immunotherapy In High Risk Populations Patients With Auto Immentioning
confidence: 99%
“…Recently Dolladille et al 41 descrip a pharmacovigilance cohort of of 24,079 irAEs associated with at least one ICI and 452 of 6123 irAEs associated with ICI rechallenges (7.4%) were analysis. This cohort study find 28.8% of recurrence rate of the same irAE.…”
Section: Resuming Ici Treatmentmentioning
confidence: 99%
See 3 more Smart Citations